On the best m-term trigonometric and orthogonal trigonometric approximations of functions from the classes L^Ψ_β,ρ - Fedorenko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain estimates exact in order for the best trigonometric and orthogonal trigonometric approximations of the classes L^Ψ_β,ρ of functions of one variable in the space L_q in the case 2 < p < q < ∞.